Evaluating Meaningful Changes in Patient‐Reported Outcome Measurement Information System–Fatigue Scores from Three Phase 3 Clinical Trials of Sarilumab for Patients With Rheumatoid Arthritis - Clifton O. Bingham; Emily Molina; Amy Praestgaard; Stefano Fiore; David Cella (ACR Open Rheumatology)
Objective The aim of this study was to evaluate changes in fatigue measured by Patient‐Reported Outcome Measurement Information System (PROMIS)‐Fatigue scores in patients with rheumatoid arthritis (RA) who received sarilumab and to assess the proportion of patients achieving clinically meaningful change. Methods Data from three phase 3 randomized controlled trials of patients with RA who received sarilumab—MOBILITY, TARGET, and MONARCH—were evaluated. The 10 RA‐relevant items from the 13‐item Functional Assessment of Chronic Illness Therapy (FACIT)‐Fatigue were scored in the PROMIS T score metric. Mean changes in 10‐item PROMIS‐Fatigue T score (PROMIS‐Fatigue 10a) were compared, proportions of patients reporting meaningful within‐person change thresholds were assessed, and results were visualized using empirical cumulative distribution function (eCDF) curves. Results Patients with RA reported high baseline fatigue. Using PROMIS‐Fatigue 10a, at week 24, patients receiving 150 or 200 mg sarilumab every other week in MOBILITY and TARGET had rapidly and significantly improved mean levels of fatigue compared to those who received placebo. When compared to patients who received adalimumab in MONARCH, patients who received sarilumab had a trend toward increased improvement. eCDF curves showed separation between active treatment versus placebo with both sarilumab doses and across the score range for improvement. Higher proportions of patients reported three‐, five‐, and seven‐point improvements in PROMIS‐Fatigue scores in groups who received active treatment. Conclusion Substantial proportions of patients with RA who received sarilumab reported meaningful change in fatigue measured by PROMIS‐Fatigue 10a over time. This study demonstrates the ability to convert FACIT‐Fatigue score onto the PROMIS T score metric, the rapid reduction in fatigue with biologic therapies, and the use of novel eCDF curves to show individual patient‐level change.